STUDI BEBERAPA ASPEK EKOLOGI BURUNG MURAI BATU DI HUTAN WISATA PANANJUNG PANGANDARAN - Sambas Basuni; Jarwadi Budi Hernowo; Moch Mulyono (Department of Forest Resources Conservation and Ecotourism - IPB University, 2005)
White rumped shama are commonly traded and raised by people due the bird’s attractive voice (The Best Song Birds). In nature, the birds is easily captured due to its possession of narrow habitat preference and strong territorial behavior. As a result, although its distribution is categorized as wide, in general, its population density is low, particularly in low land forests of Java island. Undeniably, within a not too long period, murai batu could only be found within conservation areas. Therefore, research on ecological aspects of this bird in conservation areas is very important for the purpose of conserving the bird. Ecological aspects of white rurped shara studied in this research were distribution, population density, home range, and territory. The methods used were spot mapping, tracer method, and play back method. Research results showed that distribution was in tourism forest of Pananjung Pangandaran were in places with complete strata (upper, middle and upper) and dense canopy coverage. Activities of producing sound and resting were conducted more in middle strata, while food searching was frequently conducted in upper strata. Most of the daily schedule is used for producing sound. Population density of was Pananjung Pangandaran tourism forest was 6 pairs per 10 hectares, with sizes of home range and territory were respectively 1.87 hectares and 0.79 hectares.Keywords : conservation area, habitat, home range, territory, spot mapping, tracer method, play back method.